The Effect of Financial Literacy and Manual Financial Record-Keeping Systems on the Reliability of Financial Statements in MSMEs: A Study of Fashion Stores in Palu City - Putri Nafa Bulan Aulia; Guasmin; Dicky Yusuf; Ali Supriadi (Universitas Muhammadiyah Palu, 2026)
This study aims to determine the effect of financial literacy and manual financial recording systems on the reliability of financial statements in fashion store MSMEs in Palu City. The research method used is a quantitative method with descriptive and associative approaches. The population in this study consisted of fashion store MSME owners in Palu City, with a sample of 35 respondents selected using census sampling techniques. Data collection was conducted through questionnaires. The data analysis methods used included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination tests using IBM SPSS software. The results showed that partially, the financial literacy variable did not have a significant effect on the reliability of financial statements with a significance value of 0.182 > 0.05. Meanwhile, the manual financial recording system variable had a positive and significant effect on the reliability of financial statements with a significance value of < 0.001 < 0.05. Simultaneously, financial literacy and manual financial recording systems significantly affected the reliability of financial statements with a significance value of 0.001 < 0.05 and an Adjusted R Square value of 0.814. These findings indicate that the reliability of financial statements in fashion store MSMEs in Palu City is more influenced by the implementation of routine, orderly, and consistent financial recording practices rather than solely by financial understanding.